Evaluation de l’effet insecticide et insectifuge du baume de cajou sur les insectes nuisibles du niébé Vigna unguiculata (L.) Walp. au champ - Kpoviessi, Dieudonné A.; DOSSOU, JOSEPH; CHOUGOUROU, CHÈPO DANIEL (My University, 2017)
Cowpea, Vigna unguiculata (L.)Walp.is an important crop in Benin. Many pest comprising Aphids, Thrips and Maruca constitute bottlenecks to the crop development and growth. This study aims at assessing the efficacy of the cashew’s balms as alternative and ecological methods to control these pests. The study was performed using the cowpea local variety ‘‘TAWA’’ grown at the Agronomic Faculty farm in Benin. Completed Block Design was used with six treatments: untreated; insecticide (LAMBDACE 25EC), cashew’s balms extracted while it is cold from the weaken hull of cashew; cashew’s balms extracted while it is cold from non-weaken hull of cashew;cashew’s balms extracted while it is hot from the weaken hull of cashew; cashew’s balms extracted while it is hot from non-weaken hull of cashew. Ten cowpea plants per plot have been used through the experiment from the flowering. The pests’ density was low in treated plots: the numbers of 50.91±18.63 aphids; 0.20±0.06 thrips; 2.16±0.61Maruca against133.58±11.02aphids; 0.93±0.06 thrips; 9.91±1.46Maruca respectively for hot extracted from weakened hull of cashew and untreated.Finally, the treatments’ efficacy involvedthe improvement of grain yield, (P˂0.01). These results indicated that the cashew’s balms can be used to control these pests for safe and sustainable cowpea production.
Keywords: Cashews’ balms; synthetic insecticide; insects’ pests; Vigna unguiculata; alternatives methods